Legal Protection Aspects Of Malpractice Victims Based Legal View In Indonesia - Sabungan Sibarani; Nomensen Sinamo (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2022)
Malpractice cases are a crime that is very common in Indonesia. Malpractice is basically an act of a professional that is contrary to standard operating procedures (SOP), code of ethics, and applicable laws, whether intentional or as a result of negligence that results in loss or death to others. Aspects of legal protection for patients who are victims of malpractice by doctors based on Indonesian law, namely : preventively with the existence of regulations governing malpractice, namely in the Civil Code (KUH Perdata), the Health Law, the Consumer Protection Law, the Medical Practice Law, and the Legal Code, Penal (Penal Code) and repressively the lack of action resulted in a loss, the person who performed the action imposed sanctions in the form of civil sanctions, namely to compensate both the administrator sanctions and criminal sanctions.